A study of effect of injection molding process parameters on the impact performance of plastic product fabricated by fine fillers filled LDPE - Hua Cai; Min Zeng (Functional Materials, 2016)
This study analyzed the major injection molding process parameters that affect the impact performance of low-density polyethylene(LDPE) by orthogonal experiment method. Response surface methodology was proposed to analyze the significant influence factors, and then determined optimal parameters setting of injection molding process. The results show that melting temperature and packing time are the two significant factors influence the impact performance of plastic product. Logical process parameters combinations of melting temperature, packing time and filling time are achieved by further analysis using response surface methodology. By using the optimal parameters, the arrangement of the fillers is improved, as a result, the impact performance of the filler composite is enhanced.